Improved assay for malondialdehyde determination in surimi by gas chromatography-mass spectrometry after alkaline hydrolysis - Wenjie Wang; Zhiwen Zhang; Zhigang Ke; Yuting Ding; Xuxia Zhou (Food Science of Animal Products)
Malondialdehyde (MDA) content is a primary indicator evaluating lipid oxidation level in oil-containing foods. However, total MDA compounds (tMDA) exist in both free MDA (fMDA) and bound MDA (bMDA) forms at the stage of lipid peroxidation. The traditional spectrophotometric assay quantifies the MDA after an acid hydrolysis process, only releasing limited levels of fMDA from bMDA, which named as rMDA. Considering lack of study about the effect of hydrolysis treatments on the efficiency and result accuracy in terms of MDA detection for fish products. In this study, an alkaline hydrolysis method was compared with the conventional trichloroacetic acid (TCA) hydrolysis. The results showed that the highest MDA content was obtained under hydrolysis of surimi samples with 1 mol/L NaOH for 60 min at 60 °C, which was about 2 times of that obtained from 15 g/100 mL TCA for 30 min. The alkaline hydrolysis was proved to produce more rMDA, exhibiting higher hydrolysis efficiency over the conventional method. Present works also optimized a protocol on derivatization and liquid-liquid extraction process prior to gas chromatography-mass spectrometry quantification. The hydrolysate was firstly regulated by HCl, allowing protein to fully precipitated by the following addition of TCA. This developed liquid-liquid extraction could reduce interference from presence of protein in the aqueous phase, achieving a more sensitive result with improved precision and recovery.